PEDAGOGICAL CONDITIONS OF INCREASE QUALITIES OF VOCAL AND CHORAL WORK IN THE PROCESS OF TEACHING STUDENTS (Pedagogy of Higher and Secondary Education, 2010)
It is important for receiving positive results in a vocal-choral work to know and to create pedagogical conditions of rising of the quality of the vocal-choral work in the process of pupils education. Pedagogical conditions of forming of quality of vocal-choral work mean specially created conditions owing to which deep understanding of aesthetic content of a musical composition are carried out and its influence to the personality strengthen.
Keywords: vocal-choral work; pedagogical conditions